A STUDY ON THE DIGITAL FORENSICS AND CRIMINAL PROFILING IN THE CONTEXT OF CYBERCRIME INVESTIGATIONS (International Journal of Food and Nutritional Sciences, 2022)
There is currently a sizable amount of crimes that are committed in online. Along with more recent informationor computer-related transgressions, these crimes also include more conventional ones. Examples of crimes thatcan be perpetrated online include spam email, cyber terrorism, pedophilia, and various types of child and sexualabuse. Financial fraud is an example of one that has its roots in the physical world. On the other hand, data theftand cyber espionage both totally take place online. In actuality, it represents a serious threat to the civilizationsand way of life that prevail in modern times. The fight against cybercrime requires a multifaceted strategy. Thisstudy's major objective is to do research on the digital forensics and criminal profiling in the context ofcybercrime investigations. A qualitative research methodology was used in this study. This study's findingsindicate that it's necessary to take a closer look at cross-data research that makes use of additional data sources.Thus, intelligence agents' internet-based or offline evidence, or other intelligence analysis and source, may helpnarrow a probe and meet charge breakdown criteria. Various cyber threat monitoring systems, such as theReliable, require the ability to exchange data in order to be compatible with one other. The recommendedprocedure can also be expanded to include incident news since it automatically leverages the exchange ofindicators details and the built-in risk details expression, both of which are initially critical strategic componentsof the sharing of data system.